(untitled) (Medico Legal Update, 2020)
Upper lip Curvature is a location of the oral commissure relative to the center of upper lip lower border. The aim of this study was to find the relation between gender and lip curvature. A special tool had been made to help in measurement of lip curvature. There was no significant relation between gender and curvature, however upward group was the highest one followed by straight then downward group.